The Effect of Eruca Sativa Mature Seeds on Some Reproductivity Indicators in Male Rabbits (Journal of Hama University, 2020)
The study was carried out on 30 sexually mature male rabbits aged 6 months with an average weight of 1600 gm from a local breed. The study aimed to investigate the effect of adding Eruca sativa mature seeds in different proportions with the forage mixture provided on some reproductivity indicators. The study was conducted on semen to measure the collective motility and the percentage of malformation sperm, in addition to measure the level of testosterone in blood. Three groups were employed, with six rabbits in the control group and 24 rabbits in the other groups, each for 12 rabbits. The control group was given water and a balanced fodder mix while the other study groups were fed on a balanced fodder mix with Eruca sativa seeds. (group 1 was given (%3)/Kg of fodder while group 2 was given (%6)/Kg of fodder) and the study lasted for 30 days. The samples were obtained in two phases after 15 and 30 days. The results revealed a non-significant increase in the percentage of sperm motility in group 1 and group 2 compared with each other and compared with the control group in the two phases (15, 30) days. A significant decrease (p